From Knowledge Transfer to Wisdom Cultivation: Reorienting Islamic Education in the Age of Artificial Intelligence (AI) and Post-Truth - Khasani, Fahim (Journal of Modern Islamic Studies and Civilization, 2026)
The rapid advancement of artificial intelligence (AI) and the emergence of post-truth culture have generated profound epistemic and ethical challenges for contemporary education, including Islamic education. These developments have contributed to the relativization of truth, the erosion of scholarly authority, and the increasing susceptibility of knowledge to algorithmic manipulation. In this context, Islamic education is confronted not only with the demand to adapt to technological change, but also with the need to reaffirm its foundational epistemological and ethical principles rooted in ʿilm (knowledge), ḥaqq (truth), and adab (ethical conduct). This study employs a conceptual–normative approach based on library research to examine the relationship between AI, post-truth culture, and digital ethics within the framework of Islamic education. Drawing on classical Islamic scholarship and contemporary literature on AI ethics and post-truth, the article analyzes key Islamic concepts, such as tabayyūn (critical verification), scholarly amānah (trustworthiness), ḥikmah (wisdom), and epistemic adab, and rearticulates their relevance in digital learning environments. The findings argue that Islamic education requires a paradigmatic reorientation from a transfer-of-knowledge model toward the cultivation of wisdom, positioning digital ethics and critical literacy as central components of the educational process. The study contributes to ongoing debates by proposing a framework for reorienting Islamic education that integrates technological engagement with ethical and epistemological integrity, thereby offering a normative model for addressing post-truth challenges in the age of artificial intelligence.